THE INFLUENCE OF PHILIP CAREY’S EMOTIONAL SOLATION IN WILLIAM SOMERSET MAUGHAM’S OF HUMAN BONDAGE - Adila Wandari (Universitas Katolik Widya Mandala Surabaya, 2020)
Emotional isolation is one of defense mechanism which is used to protect ones fromemotional distress by stop communicating with people. It can be triggered by socialisolation, infidelity, abuse, fear of abandonment and other trust issues whereemotional bonds have been broken. Hence, this paper aims to analyze Philip Carey’ssuffering from emotional isolation in the novel W.S. Maugham’s Of Human Bondage.The theory used is psychoanalysis theory: personal principles and defensemechanism by Sigmund Freud. These contains about conscious and unconsious sideof human and the application in their behavioral life. The research design used inthis paper is qualitative method. The technique of collecting data is library researchand in the form of written text. As for the approaches are psychological approachand sociological approach. In the end of this paper, there are results that are shownin Philip’s behavior. These are as following; becoming self-conscious, fail to controlhis most burdensome bondage: passion, and wondering about his life: seekingfreedom from every bondages.